1999
DOI: 10.1093/clipsy.6.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Depression and the ironic effects of thought suppression: Therapeutic strategies for improving mental control.

Abstract: Research indicates that depressed individuals are espccially likely t o engage in thought suppression in an attempt t o achieve mental control over the thoughts that threaten their emotional well-being. In this reporC, we examine the process and problems of thought suppression and offer several strategies designed t o enhance mental control. Strategies that improve mental control increase the availabilky and accessibility of effectlve distractions and optimize mental resources. Mental control can also be impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 73 publications
2
45
0
3
Order By: Relevance
“…Apart from the involvement of fewer men than women in the treatment procedures, the socialization processes of men might also play a role in the interpretation of the results. During their life cycle, men are usually expected to be strong and to suppress their emotions when encountering adversity, which might contribute to a higher prevalence of depression and hardly any changes in anxiety level [38].…”
Section: Emotional Reactions Of Infertile Couples During the Treatmenmentioning
confidence: 99%
“…Apart from the involvement of fewer men than women in the treatment procedures, the socialization processes of men might also play a role in the interpretation of the results. During their life cycle, men are usually expected to be strong and to suppress their emotions when encountering adversity, which might contribute to a higher prevalence of depression and hardly any changes in anxiety level [38].…”
Section: Emotional Reactions Of Infertile Couples During the Treatmenmentioning
confidence: 99%
“…19,20 Many studies have shown that attempting to suppress thoughts results in their increased activation what is known as a rebound effect. 21 Thought suppression needs motivation and massive cognitive effort that is mediated by personal affection.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Despite the prevalence of suppression as a coping strategy for unwanted thoughts, the literature suggests that it is frequently unsuccessful and indeed can be highly counterproductive (Beevers, Wenzlaff, Hayes, & Scott, 1999). In order to account for the counterproductive effects of thought suppression, Wegner (1989) has proposed the "environmental cuing hypothesis" (ECH), according to which suppression involves two cognitive control processes (Wegner & Erber, 1992).…”
mentioning
confidence: 99%